ChemInform Abstract: One‐Step Hydrothermal Synthesis of LiMn2O4 Cathode Materials for Rechargeable Lithium Batteries. Issue 28 (15th July 2014) - Lv, Xiawu; Chen, Shulin; Chen, Cheng; Liu, Lihu; Liu, Fan; Qiu, Guohong
Abstract The title cathode materials are hydrothermally prepared from aqueous mixtures of KMnO4, aniline, and LiOH (autoclave, 120—180 °C, 24 h).